Особливості використання табличного процесора Microsoft Excel для статистичного аналізу емпіричних даних - Гунько, Степан Олександрович; Hunko, Stepan O. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті розкриваються специфічні особливості, які потрібно враховувати при використанні табличного процесора Microsoft Excel у процесі статистичного аналізу емпіричних даних.В статье раскрываются специфические особенности, которые необходимо учитывать при использовании табличного процессора Microsoft Excel в процессе статистическогоанализа эмпирических данных. Основное внимание акцентируется на ранжировании эмпирических данных, особенностях вычислительных операций с помощью формул, сформированых пользователем, проведении рас-чётов точечных оценок характеристик распределений случайных величин, использовании компонента Micro-soft Excel «Пакет анализа», многоуровнености вложености функций, особенностях работы с функциями, результатом выполнения которых есть не отдельное значение, а упорядоченная группа чисел – массив, который возвращается функцией в соответствующем диапазоне ячеек электронной таблицы.In article specific features which need to be considered when using the tabular Microsoft Excel processor in the course of the statistical analysis of empirical data reveal. The main attention is focused on ranging of empirical data, features of computing operations with the help of the formulas created by the user, carrying out calculations of dot estimates of characteristics of distributions of random variables, uses of the Microsoft Excel «Analysis Package» component, a multilevel of functions, features of work with the functions which result of performance there is not a separate value, and the ordered group of numbers – the massif which comes b ack function in the corresponding range of cells of a spreadsheet.
Features of Use of the Tabular Microsoft Excel Processor for the Statistical Analysis of Empirical Data.
Keywords: емпіричні дані; статистичний аналіз; засоби Microsoft Excel для статистичного аналізу даних; empirical data; the statistical analysis; means of Microsoft Excel for the statistical analysis of data